Dekomposisi Hemiselulosa Sekam Padi Oryza sativa L Oleh Jamur Pelapuk Kayu - Welsiliana, Welsiliana (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2020)
The objective of this study was to investigate the growth and decomposition ability of wood rot fungi in reducing of hemicellulose. The study used seven fungal isolates of wood rot fungi which were inoculated into organic substrate and incubated for 30 days. The growth of fungi on the organic substrate was observed and the decrease level of hemicellulose by using the Van Soest method was analyzed. The results showed that the fastest growth of fungal isolates was seen in JM isolates that filled all organic substrates and then MKS, KSH, B, KSB, E and C isolates. The most effective hemicellulose decomposition was obtained from MKS isolates which was 79.69%.